Analisis Pekerjaan Struktur dengan Building Information Modeling (BIM) 5D pada Pembangunan Rusun Satuan Brimob Polda Kaltim - Fathurrahman Noorwahyudi; Irna Hendriyani; Martheana Kencanawati (Jurnal Talenta Sipil, 2026)
The advancement of science and technology, particularly in the field of construction technology, has had a significant impact on development. Despite the introduction of Building Information Modeling (BIM), volume and cost calculations using conventional methods are still often performed manually by consultants, which typically result in higher estimates. This study aims to implement the concept of BIM 5D using Autodesk Revit software to analyze the volume and cost of structural works in the Rusun Satuan Brimob Polda Kalimantan Timur Km.13 project, located in Balikpapan City. The research methodology involves a literature review, as well as the collection of both primary and secondary data. The subsequent stage includes structural modeling with Autodesk Revit, followed by volume and cost analysis, which are then compared with consultant calculations. Accordingly, this study applies BIM 5D to evaluate volumes and costs while benchmarking the results against conventional methods, specifically for structural works. Based on the analysis, the total structural cost estimated using BIM 5D amounts to IDR 1,158,061,415.04, whereas the consultant’s estimation reaches IDR 1,245,151,648.63, resulting in a cost difference of IDR 87,090,233.59 or 6.99%. Compared to the consultant’s method, the application of BIM 5D with Autodesk Revit produces lower and more efficient cost estimates, thereby offering a relevant and effective solution for construction cost planning.